Additive manufacturing : breakthroughs in research and practice (IGI Global, 2020)
"This book examines trends, challenges, issues, and strategies related to 3D object scanners and computer-aided design software in manufacturing processes and its impact on materials manufacturing production. It also explores the benefits of using additive manufacturing in industrial settings, as well as future outlooks for this technology"-- Provided by publisher.
Keywords: Three-dimensional printing.; Manufacturing processes.; elektronické knihy; electronic books